Genomic Insights Into New Species of the Genus Halomicroarcula Reveals Potential for New Osmoadaptative Strategies in Halophilic Archaea - Durán-Viseras, Ana; Sánchez-Porro, Cristina; Ventosa, Antonio (Frontiers in Microbiology, 2021)
Metagenomic studies on prokaryotic diversity of hypersaline soils from the Odiel saltmarshes, South-west Spain, revealed a high proportion of genomic sequences not related to previously cultivated taxa, that might be related to haloarchaea with a high environmental and nutritional flexibility. In this study, we used a culturomics approach in order to isolate new haloarchaeal microorganisms from these hypersaline soils. Four haloarchaeal strains, designated strains F24AT, F28, F27T and F13T, phylogenetically related to the genus Halomicroarcula, were isolated and characterized in detail. The phylogenomic tree based on the 100 orthologous single-copy genes present in the genomes of these four strains as well as those of the type strains of the species Halomicroarcula pellucida CECT 7537T, Halomicroarcula salina JCM 18369T and Halomicroarcula limicola JCM 18640T, that were determined in this study, revealed that these four new isolates clustered on three groups, with strains F24AT and F28 within a single cluster, and altogether with the species of Halomicroarcula. Additionally, Orthologous Average Nucleotide Identity (OrthoANI), digital DNA-DNA hybridization (dDDH) and Average Amino-acid Identity (AAI) values, likewise phenotypic characteristics, including their polar lipids profiles, permitted to determine that they represent three new species, for which we propose the names Halomicroarcula rubra sp. nov. (type strain F13T), Halomicroarcula nitratireducens sp. nov. (type strain F27T) and Halomicroarcula salinisoli sp. nov. (type strain F24AT). An in deep comparative genomic analysis of species of the genus Halomicroarcula, including their metabolism, their capability to biosynthesize secondary metabolites and their osmoregulatory adaptation mechanisms was carried out. Although they use a salt-in strategy, the identification of the complete pathways for the biosynthesis of the compatible solutes trehalose and glycine betaine, not identified before in any other haloarchaea, might suggest alternative osmoadaptation strategies for this group. This alternative osmoregulatory mechanism would allow this group of haloarchaea to be versatile and eco-physiologically successful in hypersaline environments and would justify the capability of the species of this genus to grow not only on environments with high salt concentrations (up to 30 % [w/v] salts), but also under intermediate to low salinities.